Chemical Constituents and Antimicrobial Activity of Essential Oils from Micropropagation and Field-Grown Plants of Wedelia biflora [L.] - Ahmed, Abdul Bakrudeen Ali; Magesh, J.; Idris, Siti Norayu; Mubarak, Elnaiem Elaagib; Taha, Rosna Mat (Taylor & Francis, 2018)
An efficient regeneration protocol through axillary and inter nodal explants was developed from Wedelia biflora. Explants were placed on MS medium supplemented with different treatments of cytokinins, 6-benzyladenine (BA) and kinetin (KIN) for adventitious shoot production. The highest multiple shoots (95 %; 26.4 shoots/ explant) and elongation (2.75 cm shoot length), was obtained in 1.0 BA mg L -1 in axillary node explants. The shoot was transferred to half-strength MS medium supplemented with 2.0 mg L -1 IBA showed the best root formation (85 %; 22.2 roots/shoot; 2.65 cm root length; propagate leaf d.w 1.42 g L -1 and root d.w 1.10 g L -1 ) and plantlets were successfully acclimatized in the green house. The compositions of essential oils were studied in in vitro and in vivo leaf explants and to determine their absolute and relative concentrations using GC-MS and GC-FID, respectively. In vitro and in vivo variations in composition among the essential oils were detected. Sesquiterpene and monoterpene are major components in the oil of in vitro and in vivo leaves of W. biflora. Essential oil quantification showed α-pinene (44.03 %); verbenone (15.37 %); δ-cadinene (5.48 %) of in vivo leaves; whereas α-pinene (5.02 %); verbenone (1.40 %) and δ-cadinene (3.13 %) of in vitro leave respectively. The in vitro and in vivo essential oils were analyzed by bacterial and fungal organism through disc diffusion and minimum inhibitor concentration (MIC) methods. The results were compared with reference drugs ciprofloxacin and nystatin respectively. In vitro developed plants exhibited higher sesquiterpene contents and antimicrobial activity than field grown plant.